ANALISA KOROSI PADA TANGKI REAKTOR TRIGA 2000 MENGGUNAKAN METODE INSPEKSI ULTRASONIK DAN INSPEKSI VISUAL (UNDERWATER CAMERA) - Shafira; Hendri Hestiawan; Bismantolo, Putra (UNIB Press, 2022)
A reactor is a process device where a reaction takes place, be it a chemical or nuclear reaction and not physically. Nuclear reactors are used for various purposes, namely to create, regulate, and maintain a nuclear chain reaction at a constant rate. One method of monitoring corrosion is using an ultrasonic device to measure the thickness of the tank wall and an underwater camera tool to visually see the damage that has occurred and will provide a quantitative estimate of the corrosion rate that occurs in the system by comparing the initial weight and weight after a certain time. The corrosion rate value on the TRIGA 2000 reactor wall is obtained through the weight reduction method, and has an average corrosion value of 0.10 mmpy, while the type of corrosion that occurs on the TRIGA 2000 reactor wall is the type of intergranular corrosion. protective coating by coating organic compounds (lubricant) and controlling humidity and temperature.